Socioeconomic and Parental Determinants of Child Labor in Automobile Workshops - Ali Madad; Hassan Rind; Ghulam Qadir; Moeeba Rind; Muhammad Ismail (Indus Journal of Social Sciences, 2025)
Beyond poverty, demographic, socioeconomic, and parental factors also have an impact on child labor. It is a multifaceted problem that differs depending on the culture and setting. The relationship between child labor and exploitation is not always clear-cut; rather than making generalizations, more in-depth research is needed to pinpoint the underlying causes and put specific solutions in place. This study focuses on the study of child labor working in automobile workshops. This study used the primary data, descriptive statistics, mean percentage, bar chart and pie chart were used to investigate the child labor working in automobile workshop. This study found that parent behavior, level of parent education, poor economic condition, lack of parentage, family monthly income, number of working person in a family factors have statistically significant effect on child labor. The respondents are not studying due to bad economic condition and other respondents are not studying due to lack of interest. Also concluded that most of the respondents are live with their parents and other respondents are live with their co-workers. Many respondent’s mothers are illiterate and some respondent’s mothers are literate means mothers were middle educated that is why the child labor is increasing day by day.